Sexism in English Reference Books Used by College Freshmen: Implications for Gender Equality - Luisito P. Muncada (Philippine Association of Institutions for Research, Inc., 2018)
Sexist words in the books showed an unfair treatment of the female gender. The generic term, man, refers not only to a male person but also to denote humanity. The personal pronoun is used to refer to a hypothetical person in general and accepted in Filipino society. This research is a qualitative study that used content analysis to interpret the data.  Sexism was found evident in English references. It is recommended that the sentences containing sexist language be taken out of the 12 books dissected for political correctness to make them gender fair. The textbook Board should be aware of RA 7192 (DepEd, GAD program) and CHED Memo No. 1, s. 2015, they should be gender sensitive. Policymakers should be mindful of the dynamism of language, and its importance in education must be more responsive to the needs of the time through quality language and gender sensitive.  Publishers are cautioned to exact gender-fair language from their clients so that both sexes get equal treatment in publication. Students should be alerted to sexist language, and teachers should teach gender sensitivity, even only as incidental teaching. English reference books used by the college freshmen should be reviewed, and those who found out to be sexist should be substituted with gender-fair ones.